2011
DOI: 10.1007/s10498-011-9142-3
|View full text |Cite
|
Sign up to set email alerts
|

Diel Aquatic CO2 System Dynamics of a Bermudian Mangrove Environment

Abstract: Mangrove ecosystems play an important, but understudied, role in the cycling of carbon in tropical and subtropical coastal ocean environments. In the present study, we examined the diel dynamics of seawater carbon dioxide (CO 2 ) and dissolved oxygen (DO) for a mangrove-dominated marine ecosystem (Mangrove Bay) and an adjacent intracoastal waterway (Ferry Reach) on the island of Bermuda. Spatial and temporal trends in seawater carbonate chemistry and associated variables were assessed from direct measurements … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
26
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
5
26
0
Order By: Relevance
“…A similar occurrence was noted in Mangrove Bay, Bermuda, where Zablocki et al. () observed a diel range in pH of 0.71 units in a mangrove pond.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A similar occurrence was noted in Mangrove Bay, Bermuda, where Zablocki et al. () observed a diel range in pH of 0.71 units in a mangrove pond.…”
Section: Discussionsupporting
confidence: 72%
“…Our results suggest that diel cycling in DO and pH in mangrove ponds is a general phenomenon as we observed it in both mainland Panama sites and offshore islands in Belize. A similar occurrence was noted in Mangrove Bay, Bermuda, where Zablocki et al (2011) observed a diel range in pH of 0.71 units in a mangrove pond. We expected that physical characteristics of ponds would affect the magnitude of the diel cycle.…”
Section: Physical and Biological Conditions That Affect Diel Cycling supporting
confidence: 78%
“…CO 2 -enriched seawater from mangrove habitats is then tidally exported to adjacent environments before being mixed and diluted. Zablocki et al (2011) found that the maximum diel range of pCO 2 in mangrove habitats of Bermuda was from 268 to 4,823 μatm, far beyond the range experienced in a controlled experiment designed to manipulate pCO 2 at certain target levels. The pCO 2 values at Isla Pastores ranged from 213 to 430 μatm; however, measurements were taken weekly during the mid-morning hours, and therefore, a full diel range is not represented by these data.…”
Section: Discussionmentioning
confidence: 76%
“…The P. furcata fragments used in this experiment were collected from a reef tract on Isla Pastores that, like most reefs inside the archipelago of Bocas del Toro, Panama, lies directly adjacent to a large mangrove habitat (<10 m distance). Mangrove habitats typically experience large diel variations in pCO 2 and temperature due to the shallow waters and high level of organic matter decomposition within the sediments (Borges 2003;Zablocki et al 2011). CO 2 -enriched seawater from mangrove habitats is then tidally exported to adjacent environments before being mixed and diluted.…”
Section: Discussionmentioning
confidence: 99%
“…Groundwater-derived carbon export-Previous studies have documented an inverse relationship between tidal height and DIC Kristensen et al 2008b;Zablocki et al 2011) and DOC (Lara and Dittmar 1999;Dittmar and Lara 2001) concentrations in mangrove creeks. It has been hypothesized that this tidal variation is driven by the input of groundwater enriched in DIC and DOC during the ebb tide (Dittmar and Lara 2001; Bouillon et al 2007b), with connectivity between groundwater and surface water enhanced in mangroves because of the mosaic of macrofauna burrows and organic-rich sediment layers (Ridd 1996;Mazda and Ikeda 2006).…”
Section: Discussionmentioning
confidence: 99%